2008
DOI: 10.1128/jb.01327-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Sequence Specificity Determinants Required for Processing and Control of Sex Pheromone by the Intramembrane Protease Eep and the Plasmid-Encoded Protein PrgY

Abstract: Conjugative transfer of the Enterococcus faecalis plasmid pCF10 is induced by the peptide pheromone cCF10 when recipient-produced cCF10 is detected by donors. cCF10 is produced by proteolytic processing of the signal sequence of a chromosomally encoded lipoprotein (CcfA). In donors, endogenously produced cCF10 is carefully controlled to prevent constitutive expression of conjugation functions, an energetically wasteful process, except in vivo, where endogenous cCF10 induces a conjugation-linked virulence facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 52 publications
2
68
0
Order By: Relevance
“…Clearance of SPs from the membrane might be important for protein secretion in this organism, as the B. subtilis rasP disruptant exhibits a weak defect in protein secretion (19). In accordance with our conclusion, it was reported that several peptide sex pheromones in Enterococcus faecalis are produced from the lipoprotein SP through S2P (Eep)-dependent, endoproteolytic processing (20,21). We suggest that S2P proteases in bacteria have a role equivalent to that of SPPs in higher eukaryotes.…”
Section: Discussionsupporting
confidence: 78%
“…Clearance of SPs from the membrane might be important for protein secretion in this organism, as the B. subtilis rasP disruptant exhibits a weak defect in protein secretion (19). In accordance with our conclusion, it was reported that several peptide sex pheromones in Enterococcus faecalis are produced from the lipoprotein SP through S2P (Eep)-dependent, endoproteolytic processing (20,21). We suggest that S2P proteases in bacteria have a role equivalent to that of SPPs in higher eukaryotes.…”
Section: Discussionsupporting
confidence: 78%
“…1). In uninduced cells, basal transcription from the P Q promoter generates a 380-nt transcript, Q S , which includes a single ORF (prgQ) encoding a 22-aa polypeptide processed into I and secreted into the growth medium (10). An increased intracellular level of C, resulting from addition of exogenous C or C-producing recipient cells, shifts the PrgX structure and oligomerization state from a repressing to a nonrepressing conformation, resulting in induction (11,12).…”
Section: Resultsmentioning
confidence: 99%
“…To suppress selfinduction by endogenously produced C in donors, a heptapeptide (AITLIFI) inhibitor molecule iCF10 (I) is encoded by the first gene in the polycistronic prgQ operon of pCF10 (9,10). Both C and I are synthesized initially as prepeptides that, after cleavage of the leader sequence, are secreted into the extracellular environment as active peptides (9) (Fig.…”
mentioning
confidence: 99%
“…In an intriguing interplay between sensor and signal, it has been observed that the oligopeptide pheremone signals of enterococci are generated from proteolytic processing of lipoprotein signal peptides and taken up by lipoprotein-dependent olipopeptide ABC permeases [66,67]. These oligopeptides are released from the lipoprotein signal peptide by intramembrane proteases such as Eep, most likely following the cleavage of the signal peptide from the lipoprotein precursor by the action of Lsp [68].…”
Section: Bioinformatic Prediction Of Lipoproteins In Grampositive Bacmentioning
confidence: 99%